Translation and Validation of the Chinese Version of GOHAI - May C. M. Wong, BSocSc, MPhil; Jerry K. S. Liu, BDS, BSc, MFDGP; Edward C. M. Lo, BDS, MDS, PhD (Blackwell Synergy, 2002)
To translate and validate the Chinese version of General Oral Health Assessment Index (GOHAI) for elderly in Hong Kong and to investigate factors that possibly may influence the GOHAI scores